1987
DOI: 10.1007/bf00314109
|View full text |Cite
|
Sign up to set email alerts
|

Depression and parkinson's disease: possible role of serotonergic mechanisms

Abstract: Depression is frequently encountered in Parkinson's disease and was seen to occur in 14 of 26 patients studied. The levels of 5-hydroxyindoleacetic acid (5-HIAA), the main metabolite of serotonin (5-HT), in CSF samples of the patients were significantly lower than in those of controls. However, within the group of patients the levels of 5-HIAA in CSF samples were significantly lower in the depressive subgroup compared with the non-depressive patients. Moreover, no correlation was recorded between motor disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
1
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 13 publications
1
74
1
2
Order By: Relevance
“…In fact, a decrease in serotonin concentration in basal ganglia and cerebral cortex has been observed together with low CSF 5-HIAA levels in patients with concomitant PD and depression. 41 An interaction between dopaminergic and serotoninergic systems is suggested by the fact that the administration of ritanserin, a 5-HT2 receptor antagonist, increased the dopamine neuron firing rate both in the substantia nigra and in the ventral tegmental area inducing mood and motivation enhancement. These data suggest an inhibitory control exerted by serotonin on midbrain dopaminergic neuron activity.…”
Section: The Role Of Noradrenaline and Serotoninmentioning
confidence: 99%
“…In fact, a decrease in serotonin concentration in basal ganglia and cerebral cortex has been observed together with low CSF 5-HIAA levels in patients with concomitant PD and depression. 41 An interaction between dopaminergic and serotoninergic systems is suggested by the fact that the administration of ritanserin, a 5-HT2 receptor antagonist, increased the dopamine neuron firing rate both in the substantia nigra and in the ventral tegmental area inducing mood and motivation enhancement. These data suggest an inhibitory control exerted by serotonin on midbrain dopaminergic neuron activity.…”
Section: The Role Of Noradrenaline and Serotoninmentioning
confidence: 99%
“…Indeed, degeneration of serotonergic nerve cells, decreased brain serotonin content, and alterations in the activities of various types of serotonin receptors, have all been demonstrated in post-mortem studies using neurochemical and autoradiographic techniques (Jellinger, 1991) (Scatton et al, 1983;Chen et al, 1998). Moreover, in vivo studies have consistently demonstrated reduced levels of 5-hydroxyindoleacetic acid (5-HIAA), a breakdown product of serotonin, in the cerebrospinal fluid (CSF) of PD patients (Johanson and Roos, 1967;Kuhn et al, 1996), with some studies reporting an additional reduction of 5-HIAA in depressed PD patients (Mayeux et al, 1984;Kostic et al, 1987). These findings show the involvement of serotonin in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, transcranial ultrasound studies have suggested an association with reduced brainstem raphe echogenicity and nigral hyperechogenicity in patients with depression preceding PD onset compared with nondepressed patients with PD [60]. As the PD disease progress, Lewy bodies occur with the rostral raphe, thalamus and limbic and cortical regions [15][16][17][18][19][20][21][22]61], which may result in the mediating of mood disturbances in PD [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This includes the mesocorticolimbic dopaminergic projection as well as mesocortical noradrenergic and serotonergic projections. Corticolimbic noradrenergic denervation through cell loss in the locus coeruleus and serotonergic deneravtion via serotonergic cell loss in the raphe nucleus are also likely to be important [11][12][13][14][15][22][23][24][25][26]62]. Postmortem evidence has shown a lower density of neurons in the dorsal raphe nuclei in depressed versus nondepressed patients with PD [22] and cerebro-spinal fluid measurement in vivo have shown reduced serotonin metabolite (5-HIAA) levels in depressed patients with PD [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation